Severity of drug resistance and co-existence of Enterococcus faecalis in diabetic foot ulcer infections - Shettigar, Kavitha; Bhat, Deepika V; Satyamoorthy, Kapaettu; Murali, Thokur Sreepathy (Folia microbiologica, 2018)
The genes encoding aminoglycoside resistance in Enterococcus faecalis may promote collateral aminoglycoside resistance in polymicrobial wounds. We studied a total of 100 diabetic foot ulcer samples for infection and found 60 samples to be polymicrobial, 5 to be monomicrobial, and 35 samples to be culture negative. A total of 65 E. faecalis isolates were screened for six genes coding for aminoglycoside resistance, antibiotic resistance patterns, and biofilm production. Infectious Diseases Society of America/International Working Group on the Diabetic Foot system was used to classify the wound ulcers. Majority of the subjects with culture-positive wound were recommended conservative management, while 14 subjects underwent amputation. Enterococcal isolates showed higher resistance for erythromycin, tetracycline, and ciprofloxacin. Isolates from grade 3 ulcer showed higher frequency of aac(6')-Ie-aph(2″)-Ia, while all the isolates were negative for aph(2″)-Ib, aph(2″)-Ic, and aph(2″)-Id. The isolates from grade 3 ulcers showed higher resistance to aminoglycosides as well as teicoplanin and chloramphenicol. All the 39 biofilm producers were obtained from polymicrobial wound and showed higher resistance when compared to biofilm non-producers. Higher frequency of isolates carrying aac(6')-Ie-aph(2″)-Ia in polymicrobial community showing resistance to key antibiotics suggests widespread distribution of aminoglycoside-resistant E. faecalis and their role in worsening diabetic foot ulcers.
Keywords: bakteriální léková rezistence; senioři nad 80 let; Gram-Positive Bacterial Infections; Humans; lidé; Drug Resistance, Bacterial; lidé středního věku; Middle Aged; Aged, 80 and over; Female; Male; Adult; diabetická noha; Enterococcus faecalis; mužské pohlaví; Aged; grampozitivní bakteriální infekce; Diabetic Foot; ženské pohlaví; dospělí; senioři